STUDI KUALITAS BIOETANOL DARI BAHAN BAKU KULIT PISANG SEBAGAI SALAH SATU ENERGI ALTERNATIF - Ervan Hasan Harun; Andi Shindy Keyshia; Jumiati Ilham (Universitas Muhammadiyah Gresik, 2024)
The windling availability of fossil fuels and the continuosuly increasing demand from them cause an imbalance in the stability of demand and supply. One of the efforts that can be made to replace fossil fuels is to utilize biomass energy, such as bioethanol, as substitute for fossil fuels. This study aims to determine the process of making bioethanol from banana peel by adding several variations in the composition of tape and bread yeast. Moveover, it also aims rto determine the composition of biethanol that meets the Indonesian National Standasd (SNI) 7390:2012 by conducting experiments ti determine the ethanol content, methanol content, water content, density, and viscosity. The result of the study show the best quality that can be used as a fuel substitute is the result of fermentation using 10% tape yeast from banana peel, with an ethanol content of 95.56%, methanol content of 0,52%, water content of 0,86%, density of 0,783 gr/ml, and viscosity of 1,17cP.